Exploring the glass ceiling and sticky floor in Malaysia - Wan Zainal Abidin, Wan Liyana Mariah; Mohd Noor, Zaleha; Wan Ngah, Wan Azman Saini (Canadian Center of Science and Education, 2016)
Usage of quantile regression is preferred nowadays to examine the gender earnings differentials across the earnings distribution. Based on Household Income Survey of 2009 and 2012, this paper examines the issue in Malaysia. The objective of this study is to evaluate the extent of gender earnings differentials across the earnings distribution in 2009 and 2012, whether the glass ceiling or sticky floor exists in the labour market in Malaysia. Based on the pooled quantile regression analysis, the established results indicate that the earnings gap is increasingly larger towards the bottom of the earnings distribution, a finding that is consistent with the existence of sticky floor in both years. Besides, the gender earnings gap is also accelerating between 75th to 90th percentiles, reflecting that the glass ceiling also prevails at the top of the earnings distribution in both years. Furthermore, it is noted that the impact of sticky floor is greater than glass ceiling. Nonetheless, further findings denote that the extent of sticky floor had been reduced whilst glass ceiling had increased within the period.